Analyzing environmental factors that favor the growth of the invasive brown macroalga Rugulopteryx okamurae (Ochrophyta): The probable role of the nutrient excess - Mercado, Jesus Mariano; Gómez-Jakobsen, Francisco; Korbee-Peinado, Nathalie; Avilés-Benítez, Antonio; Bonomi-Barufi, José; Muñoz, María; Reul, Andreas; López-Figueroa, Félix (Elsevier, 2022)
Time series of temperature, salinity and nutrients in the Strait of Gibraltar (SoG) were researched to analyze which factors explain the invasive success of Rugulopteryx okamurare, which has colonized wide coastal areas at the Spanish and Moroccan coasts since 2016. Temperature and salinity were higher in the SoG compared to its native habitat, implying that the alga is active during the whole seasonal cycle and grows optimally at the high salinities occurring in the SoG. Nitrate removal experiments indicate that the alga is able to linearly increase its N uptake rates following boost in nitrate concentration. Furthermore, R. okamurae N content ranged from 1.4% to 4.5% suggesting that this species has high N storage capacity potentially usable when the external N concentration decreases. These physiological characteristics would explain sharp growth of the alga in the SoG where high N concentrations are registered occasionally
Keywords: Especies exóticas invasoras; Algas; Nutrientes de las plantas; Inorganic nutrients; Nitrate uptake; Rugulopteryx okamurae; Salinity; Temperature